2020
DOI: 10.3847/2041-8213/aba0ac
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Luminosity Red Transients by Black Holes Born from Erupting Massive Stars

Abstract: We consider black hole formation in failed supernovae when a dense circumstellar medium (CSM) is present around the massive star progenitor. By utilizing radiation hydrodynamical simulations, we calculate the mass ejection of blue supergiants and Wolf–Rayet stars in the collapsing phase and the radiative shock occurring between the ejecta and the ambient CSM. We find that the resultant emission is redder and dimmer than normal supernovae (bolometric luminosity of 1040– … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…One is classified as a luminous red nova (LRN), a class of event generally interpreted as stellar mergers (Kulkarni et al 2007;Pejcha et al 2016;Blagorodnova et al 2020). Three are classified as intermediate-luminosity red transients (ILRTs), a broadly defined observational class sometimes attributed to electron-capture SNe (Botticella et al 2009;Thompson et al 2009;Moriya et al 2014), although this remains controversial; the distinction between these events and LRNs is not always obvious (Cai et al 2019), and a variety of other models exist (Pastorello et al 2007;Berger et al 2009;Bond et al 2009;Tsuna et al 2020). The lowest-luminosity non-nova transient in the BTS sample, ILRT AT2019abn, is discussed in detail by Jencson et al (2019).…”
Section: Low-luminosity ("Gap") Transientsmentioning
confidence: 99%
“…One is classified as a luminous red nova (LRN), a class of event generally interpreted as stellar mergers (Kulkarni et al 2007;Pejcha et al 2016;Blagorodnova et al 2020). Three are classified as intermediate-luminosity red transients (ILRTs), a broadly defined observational class sometimes attributed to electron-capture SNe (Botticella et al 2009;Thompson et al 2009;Moriya et al 2014), although this remains controversial; the distinction between these events and LRNs is not always obvious (Cai et al 2019), and a variety of other models exist (Pastorello et al 2007;Berger et al 2009;Bond et al 2009;Tsuna et al 2020). The lowest-luminosity non-nova transient in the BTS sample, ILRT AT2019abn, is discussed in detail by Jencson et al (2019).…”
Section: Low-luminosity ("Gap") Transientsmentioning
confidence: 99%
“…Late X-ray observations can also be an important test. Assuming that the relation Ṁ ∝ t −5/3 holds, we expect the accretion onto the BH to be super-Eddington for decades (Tsuna et al 2020). Thus continued observations in the X-ray may be a viable test that can support or falsify our interpretation of the late-time optical emission.…”
Section: Discussionmentioning
confidence: 86%
“…Mass ejection due to neutrino mass loss for BSGs has recently been studied (Fernández et al 2018;Tsuna et al 2020;Ivanov & Fernández 2021). Fernández et al (2018) and Tsuna et al (2020) estimated that mass ejection of 0.05-0.1M can occur, while Ivanov & Fernández (2021) investigated the dependence on the equation of state (EOS) at the core and found that a softer EOS would reduce the ejected mass down to ∼ 0.01M . These studies agree that the ejecta expand slowly with a bulk velocity 10 3 km s −1 , on the same order of the escape velocity at the BSG surface.…”
Section: Our Modelmentioning
confidence: 99%
“…They found that the mass of the CSM inferred from Type IIn SNe can be naturally explained if the injected energy is comparable to the binding energy of the envelope. However they find a CSM density profile close to a double power-law, with the inner part following roughly ρ ∝ r −1.5 (see also Tsuna et al 2020), shallower than a steady wind profile. While this discrepancy is interesting to investigate, interpretation of this profile was not given in their work.…”
Section: Introductionmentioning
confidence: 95%